DEIKSIS PADA SLOGAN DALAM INSTAGRAM @KOMINFOMAGELANG DAN KAITANNYA DENGAN BAHAN AJAR TEKS SLOGAN - Denik Wirawati; Isna Zumrotus Solikhah (STKIP Siliwangi, 2021)
Social media technology is a place to delivered slogan texts, one of which is through Instagram. This study explains the types and the function of deixis in the @kominfomagelang Instagram slogan that related to slogan text teaching materials. This is certainly interesting to be used as research object so that it becomes a reference for teaching materials in text learning, especially in junior high school. Knowing the deixis and slogan text by following developments in today's modern era is very necessary. This research using a qualitative descriptive method with the @kominfomagelang Instagram as a data sourced. The data collection method using a pragmatic equivalent which is equipped with a data card. Meanwhile, data analysis was carried out using referential equivalents, followed by the basic techniques of PUP (Pilah Unsur Penentu) and advanced techniques of HBS (Hubung Banding). The aim of this research is to find out the various types and functions of deixis contained in the slogan on the @kominfomagelang instagram so it can be used as an alternative teaching material in the slogan text. The results of this research show that in the @kominfomagelang instagram slogan there are three types of deixis, namely: (a) deixis Persona, (b) Place/Space Deixis, and (c) Time Deixis with the showing pronouns of person, thing, thing, temporal, and spatial function. The Indonesian language Learning in, especially in deixis, can be related and can be used as teaching material for slogan texts for VIII grade of junior high school. The research expected aim is to make students get easier to understand the deixis learning material and slogan text and add the knowledge or skills in the meaning of communication.